1994
DOI: 10.1103/physrevb.50.15796
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic noise in disordered FeZr films: Hydrogen clustering and spin-glass effects

Abstract: In mesoscopic samples of disordered Fe&oo "Zr"evaporated films with x =8, complex discrete resistance switching due to collective rearrangements of dissolved hydrogen appeared at temperatures from 4 to 300 K. In larger samples, 1% irreproducible hysteretic changes in the resistance as a function of temperature were observed near the nominal ferromagnetic transition, T& =250 K, also apparently due to clustering of dissolved H, coupled to the ferromagnetism. The unidirectional anisotropy of the lowtemperature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…thermal activation or eventually tunneling at low temperature. At high temperature T > 100K, we have observed resistance switches insensitive to magnetic field during long periods, which recall the Hydrogen hopping noise common in several metals [24]. The fractional change in resistance was between 2.10 −5 − 10 −4 , which is large for individual hopping and implied a collective motion.…”
Section: Noise Measurements As a Complementary Toolsupporting
confidence: 64%
“…thermal activation or eventually tunneling at low temperature. At high temperature T > 100K, we have observed resistance switches insensitive to magnetic field during long periods, which recall the Hydrogen hopping noise common in several metals [24]. The fractional change in resistance was between 2.10 −5 − 10 −4 , which is large for individual hopping and implied a collective motion.…”
Section: Noise Measurements As a Complementary Toolsupporting
confidence: 64%
“…For example, work by Bitko et al 32 demonstrated the existence of a signature for the spin-glass transition at high frequencies, hinting that coupling to high-frequency modes ͑such as phonons͒ may be important. In other experiments, coupling to a scalar variable-namely, the concentration of dissolved hydrogen in amorphous Fe-Zr films-resulted in suppression of the spin-glass transition, 33,34 and it may be possible to make connections with this work. FIG.…”
Section: Discussionmentioning
confidence: 78%
“…[10][11][12][21][22][23][24][25][26][27] Figures 1͑a͒ and 1͑b͒ show the dependence of S R ͑f͒ and noise-spectral slope ␣ ϵ − ‫ץ‬ ln S R ͑f͒ ‫ץ‬ ln͑f͒ on T. Above T Ϸ 6.5 K we found ordinary 1 / f-like ͑␣ Ϸ 1͒ noise with small temporal variations in the noise power. Around T Ϸ 6.5 K, S R ͑f͒ increases considerably and ␣ reaches its minimum ͑␣ Ϸ 0.5͒.…”
Section: Results and Analysismentioning
confidence: 99%